(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information about the life and work of the commentator Shikhabiddin Alusi, his interpretation of "Ruhul maa’niy fi tafsiril Qur’anil azim vas sab’ul masaniy". The article also describes the methods used in this interpretation, the important topics and the work specifics.